Tinjauan Sistematis: Pengaruh ekstrak daun kelor terhadap peningkatan hemoglobin pada remaja putri dengan anemia - Syifa Chairunnisa; A’immatul Fauziyah (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Anemia is condition of a person with hemoglobin value < 12 mg/dl. Moringa leaves are a soft woody plant with the term The Miracle Tree due to its abundant nutritional content and health benefits.Objectives: This study aims to analyze the relationship of Moringa leaf extract in increasing hemoglobin values in adolescent girls.Methods: Systematic Literature Review research with PRISMA guidelines conducted in July-September 2024. Scientific literature was obtained from SpringerLink, PubMed, and Google Scholar databases with inclusion criteria of full text, published < last 5 years, sample of adolescent girls, and experimental research using pre-posttest. A total of 10 scientific literatures were selected based on keywords in Indonesian and English, namely “Moringa leaves and anemia” OR “Moringa leaves and adolescent girls” OR “Moringa oleifera and adolescent girls” OR “Moringa leaves and hemoglobin” OR “Moringa oleifera and hemoglobin” OR “hemoglobin and adolescent girls”.Results: This study presents that consumption of Moringa leaf extract is proven to increase hemoglobin values in adolescent girls with the highest increase of +4,273 g/dl when consuming 500mg moringa capsules for 14 days. Meanwhile, the lowest increase in hemoglobin value was evident when consuming chicken dim sum made from moringa flour with an increase of 0,44 g/dl.Conclusion: Moringa leaf extract intervention is proven to increase hemoglobin values in adolescent girls. Hopefully, this research can be used as a guideline for making functional food innovations to prevent anemia.